2017
DOI: 10.1039/c7cp04435f
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution natural abundance 33S MAS NMR study of the cementitious mineral ettringite

Abstract: Despite the widespread occurrence of sulfur in both natural and man-made materials, the S nucleus has only rarely been utilised in solid-state NMR spectroscopy on account of its very low natural abundance (0.76%), low NMR frequency (ν = 30.7 MHz at B = 9.4 T), and significant nuclear quadrupole moment (spin I = 3/2, Q = -69.4 mb). Satellite-transition magic angle spinning (STMAS) is an NMR method for obtaining high-resolution spectra of half-integer quadrupolar nuclei (spin I > 1/2) in solids and is notable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The isotropic shifts of the three SO 4 2-were only separated by $1 ppm and needed the differences in the larger second-order quadrupolar shifts at the lower field to really separate them (Figure 9). [171] Sulphur plays an important role in the internal processes of the Earth and is transported in hydrous silicate melts where its oxidation state can range widely from −2 to +6, which has a profound effect on its chemistry. A range of silicate glasses were investigated, requiring isotopic enrichment as typically only 0.5% sulphur was present.…”
Section: Sulphur-33mentioning
confidence: 99%
See 1 more Smart Citation
“…The isotropic shifts of the three SO 4 2-were only separated by $1 ppm and needed the differences in the larger second-order quadrupolar shifts at the lower field to really separate them (Figure 9). [171] Sulphur plays an important role in the internal processes of the Earth and is transported in hydrous silicate melts where its oxidation state can range widely from −2 to +6, which has a profound effect on its chemistry. A range of silicate glasses were investigated, requiring isotopic enrichment as typically only 0.5% sulphur was present.…”
Section: Sulphur-33mentioning
confidence: 99%
“…These are titanium-based, with current technology using an MgCl 2 support and TiCl 4 catalyst. An initial report using 35 Cl to examine the MgCl 2 support, as for 25 Mg (vide supra) showed both the effect of ball milling used in activation and that the particle morphology induced a [171] Reproduced from the reference with permission of the copyright holder preferred orientation in the rotor and hence a curious lineshape. [145] Nevertheless, it showed signal enhancement techniques and DFT calculations could be applied to these systems.…”
Section: Compoundmentioning
confidence: 99%
“…Indeed, in many such systems the precise redox mechanisms remain poorly understood, with direct evidence of S 2 2− coming primarily from Raman spectroscopy. 8 Whereas many prior studies on Li-ion battery materials have employed 6/7 Li solid-state NMR experiments, 9,10 very few solid-state 33 S NMR studies of any kind have been reported, due to the low gyromagnetic ratio (1 13 ⁄ that of 1 H), very low natural abundance (0.76%), and large quadrupolar moment (I = 3/2) of 33 S. [11][12][13][14][15] Recent 33 S NMR studies of Li-S and Mg-S battery systems have identified the discharge products (Li2S and MgS), 16,17 which contain S 2− in tetrahedral environments, but the technique has not been applied to study sulfide-based conversion electrodes. Previous 33 S NMR studies on functional inorganic sulfides include TM disulfides (e.g., MoS2 and TiS2), where trigonal pyramidal S 2− environments give rise to large quadrupolar coupling constants (CQ) of 2-10 MHz and correspondingly broad NMR powder patterns via second-order quadrupolar (SOQ) broadening of the I = 3/2 central transition.…”
mentioning
confidence: 99%
“…This is a challenge, especially in sulfated compounds, as 33 S NMR requires the detection of a low-sensitivity nucleus with a low natural abundance of only 0.33%. 180 Due to these limitations, implementing 33 S HMBC experiments to link the signals to the corresponding carbons is practically unfeasible.…”
Section: Synthesis Of Fully Sulfated Monoacyl Analoguementioning
confidence: 99%